2018
DOI: 10.1177/1741143218781064
|View full text |Cite
|
Sign up to set email alerts
|

Transformational school leadership as a key factor for teachers’ job attitudes during their first year in the profession

Abstract: Teacher attrition is a global concern that is particularly prevalent among beginning teachers. Teachers’ intrinsic motivation to teach, affective organisational commitment and job satisfaction are considered job attitudes that stop them from dropping out of the profession. This study explores the interplay between factors at the school level (i.e. transformational leadership of the principal, professional collegial support) and the teacher level (i.e. self-efficacy) influencing these job attitudes. A sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 114 publications
(219 reference statements)
2
41
0
2
Order By: Relevance
“…Employees’ work attitudes serve as an important emotional factor that creates various and multiple commitments. Teachers with a stronger commitment to their profession and organization are expected to be more effective and to address their students’ needs more efficiently (Thomas et al, 2020 ). In this study, we investigated several aspects of work attitudes, as the literature shows the importance of these particular attitudes among teachers in general, and more specifically, among teachers working with students at risk (Castrén et al, 2017 ).…”
Section: Teachers’ Work Attitudesmentioning
confidence: 99%
“…Employees’ work attitudes serve as an important emotional factor that creates various and multiple commitments. Teachers with a stronger commitment to their profession and organization are expected to be more effective and to address their students’ needs more efficiently (Thomas et al, 2020 ). In this study, we investigated several aspects of work attitudes, as the literature shows the importance of these particular attitudes among teachers in general, and more specifically, among teachers working with students at risk (Castrén et al, 2017 ).…”
Section: Teachers’ Work Attitudesmentioning
confidence: 99%
“…Previous studies showed that TSL is positively related to teacher commitment (e.g., Li & Liu, 2020;Thomas et al, 2018), classroom practices (Leithwood & Jantzi, 1999;Leithwood & Mascall, 2008;Thoonen et al, 2011), and to students' academic success (Sun & Leithwood, 2012). However, even though these findings suggest that TSL might be an important factor in shaping teacher effectiveness, research in this field is still scant.…”
Section: Transformational School Leadership and Instructional Qualitymentioning
confidence: 99%
“…to strengthen those relationships as a possible solution to the teacher attrition problem. However, while there is evidence that some administrators have employed such efforts with some success in their schools, such successes have not made a dent in teacher attrition levels on a large scale [19].…”
Section: Summary Of Teacher Attrition Researchmentioning
confidence: 99%